Studying the Leadership Styles in the UAE - yunus, Ahmad rozelan bin; majid, Izaidin bin abdul; Mazroui, Abdullah Al (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the authors have reviewed and summarized the main leadership styles in management. These leadership styles are represented by the participative style and democratic leadership styles that usually empower employees and gives them more freedom to maneuver on the one hand. On the other hand, there is the authoritative style, which is a leadership style that limits the creativity and action taking by employees. Then, the researchers conducted a pilot study to have a preliminary idea about the attitudes of leaders regarding two leadership styles, each on each end of a spectrum; namely the participative style and the authoritative style.